The Caring for Bedbound Old Adult: A Systematic Review - Vudhironarit, Suwanna; Pommala, Walainaree (Journal of The Royal Thai Army Nurses, 2021)
The aim of this systematic review of bedbound elderly caring research articles was to improve the quality of life among bed-bound elderly issues, including physically, mentally, social relationships and environment. This systematic review was conducted limited to original research articles that were published between 2011 and 2020. The articles focused on bedbound elderly caring. There were seven research articles met the inclusion both criterias with the PICos framework for qualitative research and the PICO framework for quantitative research. The data from each study were extracted by two independent reviewers. Data Synthesis showed the caring on improve the quality of life among bed-bound elderly separate in to five parts. These were integrated together. 1) bed bound elderly self-care as self-care activity and cooperate activity for self-care, 2) by their family care, the someone was accepted as main caregiver and everyone in the family was developed to be caregivers. 3) by health volunteers, 4) by the health service system by monitoring, suggesting, screening and referring to the level of care needs, and 5) community generosity such as neighbors, community leaders, Elderly club and local government organizations they supported for bedbound elderly caring for quality of care including quality of life Literature review reveals that some health care activity of organizations in health service system and the local government organizations was complicated. That was advising, teaching, and enhancing the competence of caregivers. They should have cooperated to only one which improves the quality of life of bedridden older adult.